PENGABDIAN KEPADA MASYARAKAT BERBASIS PEMBELAJARAN INDIVIDUAL BERORIENTASI OUTCOME DALAM PELATIHAN BAHASA INGGRIS DUNIA KERJA DI SAS ENGLISH LABORATORY MEDAN - Muhammad Danial; Ananda Pasha Salsabila; Ajeng Tria Wasesha Nasution; Ratna Sari Dewi (LPPI UMN AL WASHLIYAH, 2026)
This community service program aimed to improve workplace English skills through outcome-oriented individualized learning at SAS English Laboratory Medan. The program applied a training and mentoring approach using one-to-one instruction, beginning with a needs analysis, followed by a pre-test, targeted professional communication training, and evaluation through a post-test and participant feedback. The training materials covered professional self-introduction, job interview simulations, formal workplace expressions, and job-related vocabulary. The results indicated an improvement in participants’ workplace English communication skills, particularly in speaking fluency, appropriate use of professional expressions, and confidence. Individualized learning enabled tutors to provide immediate and needs-based feedback, making the training process more effective and adaptive. This program contributes a flexible and measurable model for workplace English training to support productive-age community members in meeting professional communication demands.